2014
DOI: 10.3414/me13-01-0053
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Validity of Mapping between Drug Indications and ICD-10

Abstract: Considering no differences in the F1 scores, both approaches may be used in practice for mapping drug indications to ICD-10. However, in terms of consistency, time and manpower, better results are expected from the indirect terminology based approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…The application of the terms, to the statements, was done via a computer application designed by an information technology specialist. It is an alternative way to keep the data as consistent as data from the legacy approach, but more efficient [11]. There were three more measures to keep the process valid.…”
Section: Reliability and Validity Of Data Managementmentioning
confidence: 99%
“…The application of the terms, to the statements, was done via a computer application designed by an information technology specialist. It is an alternative way to keep the data as consistent as data from the legacy approach, but more efficient [11]. There were three more measures to keep the process valid.…”
Section: Reliability and Validity Of Data Managementmentioning
confidence: 99%
“…Two-thirds of the coding systems identified in the review are used in North America and/or Europe. Despite the concentration of coding system use in the Western countries with sophisticated healthcare infrastructures, there is still great variability in coding system use between countries and geographic regions, including country-specific modifications or multiple versions [14,23,24,30,82,83,[180][181][182][183][184]. Most of the country-specific modifications exist as a result of linguistic differences between countries using the coding systems.…”
Section: Discussionmentioning
confidence: 99%
“…16% (n=9) of the identified coding systems presented country-specific modifications or multiple versions (due to updates and revisions of code definitions, consolidation between systems, etc. ): Diagnosis-Related Groups (DRGs), ICD-10, ICD-9, ICD-O, International Classification of Primary Care (ICPC), Assistive Products for Persons with Disability -Classification and Terminology (ISO 9999), Nordic Medico-Statistical Committee (NOMESCO) classification of surgical procedures (NCSP), and Read codes (▶ Table 1) [11,14,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. 13% (n=7) of the identified coding systems were designed for specific conditions or therapeutic areas, including the American Joint Committee on Table 1 List of all coding systems identified in the review, abbreviated name and number of articles captured in the review (characteristics and applications).…”
Section: Coding System Characteristicsmentioning
confidence: 99%
“…[7][8][9] In previous studies it has been shown to be feasible for prescription data to be used to derive patients' diagnoses (mapping from ATC to ICD codes). [10][11][12] However, many of these studies mainly focused on avoiding billing mistakes or documentation errors. 10,11 To demonstrate that this approach may also help to improve medication safety, we performed a proof of principle analysis.…”
Section: Introductionmentioning
confidence: 99%